Factors affecting occupational distress and its relationship to teaching satisfaction of physical education teachers - Fernandez, Pamela; Sanchez, Lester; Tongol, Jonathan; Zabala, Ian; Lobo, Joseph; Bernardo, Bryan Dale; Celis, Michael Louie (Edu Sportivo: Indonesian Journal of Physical Education, 2023)
The COVID-19 pandemic has wrought substantial challenges on individuals and societies, including the academe. The pandemic required a sudden shift to remote learning. Teachers were called upon to support students' academic development and well-being throughout this shift while navigating adversity and stress in their own lives. The researchers aim to describe the factors affecting the relationship between Occupational Distress (OD) and Teaching Satisfaction (TS) among Physical Education teachers handling Junior and Senior High Schools in Angeles City with 150 respondents through a self-administered survey. Purposive or Convenience sampling was utilized to recruit respondents, while descriptive and inferential statistics were used to analyze the data. The researchers found that most respondents are women between 22 to 29 years old, female, and single. In terms of history, the majority of the respondents are ranked as Teacher I, working in public school, with a salary of 20,001-30,000 range; most of them have their bachelor's degree, handling junior high school students, and working for one (1) - three (3) years. The result shows that respondents' OD level is low while their level of TS is moderate. The study results show a significant moderate correlation between Teacher's Occupational Distress and Teacher's Teaching Satisfaction. Specifically, in terms of each variable, age and type of school substantially affect the Teachers' Occupational Distress. On the other hand, no variable significantly affects the Teachers' Teaching Satisfaction in terms of the demographic profile and teaching history.